2019
DOI: 10.3389/fmicb.2019.01054
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Acquisition, Rather Than Stress Response Over Diel Cycles, Drives Microbial Transcription in a Hyper-Arid Namib Desert Soil

Abstract: Hot desert surface soils are characterized by extremely low water activities for large parts of any annual cycle. It is widely assumed that microbial processes in such soils are very limited. Here we present the first metatranscriptomic survey of microbial community function in a low water activity hyperarid desert soil. Sequencing of total mRNA revealed a diverse and active community, dominated by Actinobacteria. Metatranscriptomic analysis of samples taken at different times over 3 days indicated that functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 77 publications
6
56
1
Order By: Relevance
“…Soil nitrate is depleted of 15 N in Antarctic soils [13], and our data support previous findings that soil nitrate in the desert sub-surface may be an essential reservoir of bioavailable nitrogen used by microorganisms to overcome nitrogen deficiency [69]. Interestingly, a recent metatranscriptomic study of microbial functionality in desiccated hot desert soils [70] showed high levels of nitrate reductase gene expression but little or no nitrogenase gene expression, suggesting that nitrate was also the primary source of metabolic N in this edaphic environment.…”
Section: Discussionsupporting
confidence: 89%
“…Soil nitrate is depleted of 15 N in Antarctic soils [13], and our data support previous findings that soil nitrate in the desert sub-surface may be an essential reservoir of bioavailable nitrogen used by microorganisms to overcome nitrogen deficiency [69]. Interestingly, a recent metatranscriptomic study of microbial functionality in desiccated hot desert soils [70] showed high levels of nitrate reductase gene expression but little or no nitrogenase gene expression, suggesting that nitrate was also the primary source of metabolic N in this edaphic environment.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, these primary producers are low in abundance in exposed surface soils, which are instead dominated by chemoheterotrophs from phyla such as Actinobacteriota, Acidobacteriota, and Proteobacteria (10,15,16). Most of these bacteria are thought to live in dormant states during dry periods (6,7,17); while they have detectable transcriptional and metabolic activity (18)(19)(20), cells primarily expend energy for maintenance rather than growth. Rainfall pulses stimulate microbial activity and succession over short timescales, and the frequency and intensity of these events are thought to be major factors determining the composition and function of desert microbial communities over longer timescales (21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…In the present study, we detected several stress response genes associated with cold-shock, heat-shock and osmotic pressure, though only a small fraction was co-occurring with MGEs. The stress response is highly transcribed in potentially active microbial communities from desert soils but it seems that nutrient acquisition is a more critical factor [4]. Even so, rpoE co-occurring with MGEs was the most abundant gene identified with GhostKOALA in the present study.…”
Section: Stress Response Heavy Metal and Antimicrobial Resistance Gementioning
confidence: 53%
“…For example, the gene coding for dihydrolipoyl dehydrogenase was the most abundant gene related to energy production co-occurring with MGEs. This enzyme, involved in the TCA cycle, has been recognized as a central step in the carbohydrate metabolism in the Nabim Desert [4]. The authors of this study suggested that nutrients acquisition (nitrogen, phosphorus and sulfur assimilation and carbon fixation) rather than the stress response has a central role in the transcriptional activity.…”
Section: Mges and Co-occurring Genesmentioning
confidence: 83%
See 1 more Smart Citation